Does sodium-bicarbonate ingestion improve simulated judo performance? - Artioli, G. G.; Gualano, B.; Ferreira Coelho, D.; Braga Benatti, F.; Whyte Gailey, I.; Lancha Jr, A. H. (International Journal of Sport Nutrition and Exercise Metabolism, 2007)
The aim of the present study was to investigate whether preexercise sodium-bicarbonate ingestion improves judo-related performance. The study used 2 different protocols to evaluate performance: 3 bouts of a specific judo test (n = 9) and 4 bouts of the Wingate test for upper limbs (n = 14). In both protocols athletes ingested 0.3 g/kg of sodium bicarbonate or placebo 2 h before the tests. Blood samples were collected to determine lactate level, and levels of perceived exertion were measured throughout the trials. The study used a double-blind, counterbalanced, crossover design. Ingestion of sodium bicarbonate improved performance in Bouts 2 and 3 of Protocol 1 (P < 0.05), mean power in Bouts 3 and 4 of Protocol 2 (P < 0.05), and peak power in Bout 4 of Protocol 2 (P < 0.05). Ingestion of bicarbonate increased lactate concentration in Protocol 1 (P < 0.05) but not in Protocol 2. Ratings of perceived exertion did not differ between treatments. In conclusion, sodium bicarbonate improves judo-related performance and increases blood lactate concentration but has no effect on perceived exertion.